2013
DOI: 10.1038/nmat3785
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oxidation of nanoparticles through strain-mediated ionic transport

Abstract: Geometry and confinement effects at the nanoscale can result in substantial modifications to a material's properties with significant consequences in terms of chemical reactivity, biocompatibility and toxicity. Although benefiting applications across a diverse array of environmental and technological settings, the long-term effects of these changes, for example in the reaction of metallic nanoparticles under atmospheric conditions, are not well understood. Here, we use the unprecedented resolution attainable w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 28 publications
5
101
3
Order By: Relevance
“…These observations are in agreement with what has been found also at the interface of Au-Fe 3 O 4 composites [48,49], Co/Co 3 O 4 nanooctahedra [25], and Fe oxidized cubic NP [50], suggesting that lattice mismatch correlates with changes in magnetic anisotropy. There is also evidence that lattice strain induced by acoustic waves applied to some magnetic structures [51,52] can influence the value of the anisotropy constant and its easy axis.…”
Section: Magnetic Characterizationsupporting
confidence: 92%
“…These observations are in agreement with what has been found also at the interface of Au-Fe 3 O 4 composites [48,49], Co/Co 3 O 4 nanooctahedra [25], and Fe oxidized cubic NP [50], suggesting that lattice mismatch correlates with changes in magnetic anisotropy. There is also evidence that lattice strain induced by acoustic waves applied to some magnetic structures [51,52] can influence the value of the anisotropy constant and its easy axis.…”
Section: Magnetic Characterizationsupporting
confidence: 92%
“…3(g)-3(i). The data suggests that Ni nanoparticles possess the thinnest oxide shell with a thickness of about 1 nm, while Co and Fe nanoparticles develop an oxide shell of 2 to 3 nm in agreement with previous studies [60,66,67]. The actual particle sizes in UHV during the X-PEEM and RHEED investigations might therefore be smaller by about 1-2 nm when compared to the ex situ AFM results presented in Figs.…”
Section: B Structural Characterization By Means Of Rheedsupporting
confidence: 91%
“…Stacking fault energies in bcc Fe are comparably high; therefore, such defects are likely metastable in nanoparticles as for dislocations. In fact, stacking faults or twinning have been observed thus far only in bulklike systems under high mechanical stresses but not in bcc Fe nanoparticles [16,60,67,94]. Similarly, there is currently no evidence for dislocations or other defects in bcc Fe nanoparticles, including the present HR-STEM results.…”
Section: -9contrasting
confidence: 56%
“…Even though the study of the surface of such materials is in its infancy there are hints that novel effects occur. For example, Pratt et al [614] recently showed that strain at the surface of iron oxide nanocubes leads to increased diffusion of cations, potentially explaining enhanced oxidation rates that have been observed for Fe nanoparticles. It would be fascinating to see if cuboid Fe 3 O 4 nanoparticles exposing (001) facets exhibit the SCV reconstruction, and whether similar Fe rich terminations appear in reducing conditions.…”
Section: Realistic Materialsmentioning
confidence: 99%